-6u+3(u+4)=-18

Simple and best practice solution for -6u+3(u+4)=-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6u+3(u+4)=-18 equation:


Simplifying
-6u + 3(u + 4) = -18

Reorder the terms:
-6u + 3(4 + u) = -18
-6u + (4 * 3 + u * 3) = -18
-6u + (12 + 3u) = -18

Reorder the terms:
12 + -6u + 3u = -18

Combine like terms: -6u + 3u = -3u
12 + -3u = -18

Solving
12 + -3u = -18

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + -3u = -18 + -12

Combine like terms: 12 + -12 = 0
0 + -3u = -18 + -12
-3u = -18 + -12

Combine like terms: -18 + -12 = -30
-3u = -30

Divide each side by '-3'.
u = 10

Simplifying
u = 10

See similar equations:

| 8y=7y+1 | | x^2+x+6=4x+4 | | 4r^2+28r=0 | | 2/3•3=6/3 | | 2/3-1/6x=5/12 | | 11b+7=4 | | 4/3=n-4/n | | 49=6x+x | | 3n-3=-8(5+5n) | | 5-3a=2 | | 45=4x^2+x^2 | | 50=x+22 | | 3n-9n=0 | | 3z/8-7=-5 | | 10(2x+3)=50 | | 0.4y+5.6=2.4 | | 5n-21=-111 | | x+2=2x+50 | | 14-6n=-8(-7n+6) | | (8/7)=(3x/86) | | cos(55)=x/12 | | 5(1+y)=15(1-y) | | -7=-21-x/4 | | F=8(2)+9(-5) | | -20-2n=8+5n | | (X^2-576)=(3x+4) | | -9-6v=4v+93 | | 8p-4=9p-8 | | 0.52(12x+24)+3x= | | 3z+6=8z-45 | | 8w+12=6w+4 | | 5x+6=15-2x |

Equations solver categories